Functional reef fish groups of the Mexican Caribbean: implications of habitat complexity - Rosalía Aguilar-Medrano; Jesús Ernesto Arias-González (Revista Mexicana de Biodiversidad)
The Caribbean Sea is considered a unique biogeographic region and is among the top 5 world hotspots of marine biodiversity. Yet, over the last years it is among the regions where the most serious declines in terms of reef area, health, and productivity is occurring. In this study, the coral reef fish community of the Mexican Caribbean was analyzed and classified into functional groups. The aims of this study were: 1) determine the functional relationships of the fish community based on diet and morphology, and 2) determine the extent of the influence of habitat complexity and the protection of the Sian-Ka'an reserve on the fish richness and functional diversity of the ecosystem. Eleven reef localities of the Yucatán Peninsula and 160 species were analyzed. Twenty-eight functional groups were described for both ecological and morphological variables. Our results indicate that variation in habitat complexity was a significant factor related to fish richness and functional diversity; however, the protection of the reserve does not show a relationship with any of the response variables. On the other hand, the slope is the reef zone with the highest fish richness in all localities, creating a belt of richness and connectivity in the whole area.